PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE, DAN UKURAN DEWAN KOMISARIS PADA PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Pradnyani, I Gusti Agung Arista; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi; Vol 11 No 2 (2015), 2015)
The implementation of corporate social responsibility is intended to minimize the adverse impacts of doing businesses activities on social and environmental aspects. This study examines variables influencing CSR which include firm size, profitability, leverage, and board size. This study uses a purposive sampling method and obtain a sample of 66 companies. Non-participant observation method is used to collect data. Multiple linear regression is conducted to analyze data.  The results show that profitability and size of the board of commissioners expresses a positive effect on CSR. The tests also suggest that the size of the company does not affect CSR because all companies are equally revealing CSR. Leverage also has no effect on CSR indicating that the management would optimize profit to avoid debtholders’ concerns.
Keywords: Corporate Social Responsibility (CSR), firm size, profitability, leverage, board size